Pengaruh Product Knowledge Dan Price Terhadap Keputusan Pembelian Konsumen Pada Produk The Capital - Erni Saputri Halim; Christian Herdinata (BIP's JURNAL BISNIS PERSPEKTIF, 2017)
The purpose of this research is to identify the influence of product knowledge and price on the customer purchasing decision of product The Capital. The population of this study is all consumers of product The Capital. Convenience Sampling is used to select 45 samples. This study also uses quantitative methods. SPSS 16.0 is used as quantitative data analysis tool.Quantitative research results show that Product Knowledge and Price significantly influence the Customer Purchasing Decision of The Capital. The significant influence show that consumer with higher product knowledge will increase potential of purchasing decision of products The Capital.